The relationship between diabetes and clinical outcomes in COVID-19: a single-center retrospective analysis - Fox, Tamaryn (Acta Diabetol, 2020)
AIMS: Coronavirus disease 19 (COVID-19) has become a pandemic. Diabetic patients tend to have poorer outcomes and more severe disease (Kumar et al. in Diabetes Metab Syndr 14(4):535–545, 2020. 10.1016/j.dsx.2020.04.044). However, the vast majority of studies are representative of Asian and Caucasian population and fewer represent an African-American population. METHODS: In this single-center, retrospective observational study, we included all adult patients (> 18 years old) admitted to Einstein Medical Center, Philadelphia, with a diagnosis of COVID-19. Patients were classified according to having a known diagnosis of diabetes mellitus. Demographic and clinical data, comorbidities, outcomes and laboratory findings were obtained. RESULTS: Our sample included a total of 355 patients. 70% were African-American, and 47% had diabetes. Patients with diabetes had higher peak inflammatory markers like CRP 184 (111–258) versus 142 (65–229) p = 0.012 and peak LDH 560 (384–758) versus 499 (324–655) p = 0.017. The need for RRT/HD was significantly higher in patients with diabetes (21% vs 11% p = 0.013) as well as the need for vasopressors (28% vs 18% p = 0.023). Only age was found to be an independent predictor of mortality. We found no significant differences in inpatient mortality p = 0.856, need for RRT/HD p = 0.429, need for intubation p = 1.000 and need for vasopressors p = 0.471 in African-Americans with diabetes when compared to non-African-Americans. CONCLUSIONS: Our study demonstrates that patients with COVID-19 and diabetes tend to have more severe disease and poorer clinical outcomes. African-American patients with diabetes did not differ in outcomes or disease severity when compared to non-African-American patients.